MTNR-1A Gene Polymorphism in Two Tropical Sheep breeds of South India - Vibha, CR; Ramakrishnappa, Nagaraja; Naveen, GS; Jayashree, R; Ravindranathe, BM (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was carried out to evaluate the genetic polymorphism in Ovine MTNR1A of two tropical breeds ie., highly prolific NARI Suwarna sheep and Mandya sheep from southern peninsular region of India with respect to differential fertility. Fifty animals from each breed were randomly selected and subjected to RsaI-RFLP analysis of exon-2 of Ovine MTNR1A. The study revealed monomorphic patterns in all the animals for both the breeds. PCR amplicon of 824 bp fragments with four cut sites at 53 bp, 320 bp, 343 bp and 754 bp, resulted in 411 bp, 267 bp, 70 bp, 53 bp and 23 bp. Only presence of CC genotypes at rs406779174 SNP of Ovine MTNR1A in both the breeds supports non-seasonality in breeding of these animals and no association of SNP with increased fecundity of NARI Suwarna sheep over Mandya sheep. seasonal reproduction (Gall et al., 2002). Reproductive efficiency in sheep often varies among the breeds, which is largely influenced by genetic and environmental factors. Seasonal variation in reproductive activity is controlled by photoperiod in sheep (Thiery et al., 2002). The non-seasonal sheep breeds exhibit reproductive responses to improved nutrition irrespective of photoperiod, whereas the seasonal breeds respond to nutrition only during breeding season (Hotzel et al., 2003). The endocrine signal, circadian rhythm of melatonin secretion is responsible for mediating the effects of photoperiod on the hypothalamo pituitary axis and plays an important role in regulation of Reproductive effects of melatonin are mediated via ligand specific guanine nucleotide-binding protein (G-protein) coupled receptors located in the hypophyseal pars tuberalis (Ebisawa et al., 1994).
Keywords: Ovine; MTNR1A; PCR-RFLP; RsaI-RFLP,; Mandya sheep; NARI -Suwarna